Tales ebook Short stories featuring ian rutledge and bess crawford. - Todd, Charles (2015)
Now published together for the first time: Charles Todd's absorbing short stories—"The Kidnapping," "The Girl on the Beach," "Cold Comfort," and "The Maharani's Pearls"—featuring everyone's favorite Scotland Yard Inspector Ian Rutledge and intrepid battlefield nurse Bess Crawford. These vibrant tales transport readers from the home front in Great Britain where ominous clouds of war will soon lead to the trenches of France, to the bloody front lines where Lieutenant Rutledge must risk his life to save his men. And finally to the exotic, dangerous India of Bess Crawford's youth. Together they create a fascinating glimpse into the extraordinary backgrounds of two of mystery's most popular characters.